2016
DOI: 10.1038/srep30492
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the abundance and diversity of abyssal megafauna in a polymetallic-nodule region in the eastern Clarion-Clipperton Zone

Abstract: There is growing interest in mining polymetallic nodules in the abyssal Clarion-Clipperton Zone (CCZ) in the Pacific. Nonetheless, benthic communities in this region remain poorly known. The ABYSSLINE Project is conducting benthic biological baseline surveys for the UK Seabed Resources Ltd. exploration contract area (UK-1) in the CCZ. Using a Remotely Operated Vehicle, we surveyed megafauna at four sites within a 900 km2 stratum in the UK-1 contract area, and at a site ~250 km east of the UK-1 area, allowing u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
248
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(273 citation statements)
references
References 49 publications
(100 reference statements)
14
248
2
1
Order By: Relevance
“…Paleodictyon traces very similar to those observed in APEI-6 were identified during the ABYSSLLINE project in images from the UK-1 exploration claim area and the BEPIRB^area situated 250 km to the east of UK-1 (C.R. Smith, D. Amon and A. Ziegler personal communication; site locations in Amon et al 2016). Rona and Merrill (1978) reported a similar size (∼50 mm) for Paleodictyon at the MAR, although the number of holes in the arrays was greater (10 × 10 × 10 to 13 × 13 × 12).…”
Section: Morphologymentioning
confidence: 99%
“…Paleodictyon traces very similar to those observed in APEI-6 were identified during the ABYSSLLINE project in images from the UK-1 exploration claim area and the BEPIRB^area situated 250 km to the east of UK-1 (C.R. Smith, D. Amon and A. Ziegler personal communication; site locations in Amon et al 2016). Rona and Merrill (1978) reported a similar size (∼50 mm) for Paleodictyon at the MAR, although the number of holes in the arrays was greater (10 × 10 × 10 to 13 × 13 × 12).…”
Section: Morphologymentioning
confidence: 99%
“…Pressure from fishing has also increased since the mid-20 th century on seamounts and along continental margins, and there is now strong evidence that many deepwater fish species (e.g., rockfish, Greenland halibut, lings and tusks, orange roughy, sablefish and blue grenadier) have been severely exploited through trawling and longlining, with some species having been fished to commercial extinction (e.g., pelagic armourhead; Koslow et al 2000). There is also extensive interest in mineral mining at hydrothermal vent systems along mid ocean ridges and back arc basins, bathyal seamounts and polymetallic nodule areas at abyssal depths, as well as for phosphorites on margins (Mengerink et al, 2014;Thurber et al, 2014;Wedding et al, 2015;Amon et al, 2016;Levin et al, 2016;Vanreusel et al, 2016). Deep-sea sediments and organisms are also sinks for a variety of chemical pollutants, including persistent organochlorine pollutants (e.g., PCBs), which may have toxic effects for a variety of fauna at high concentrations (Froescheis et al, 2000;Looser et al, 2000;Ramirez Llodra et al, 2011).…”
Section: Implications Of Climate Forcing On Societal Uses and Values mentioning
confidence: 99%
“…3; Thiel et al 1993;Veillette et al 2007;Vanreusel et al 2016). A recent study by Amon et al (2016b) suggested that more than half of megafaunal species in the CCZ depend on nodules as a hard substrate. Furthermore, nodule areas seem to contain higher densities of mobile megafauna compared to those lacking nodules (Amon et al 2016b;Vanreusel et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The variety of habitats has been thought to promote higher diversity of associated benthic communities compared to abyssal areas elsewhere (Ramirez-Llodra et al 2010;Janssen et al 2015;Amon et al 2016b;Vanreusel et al 2016).…”
Section: Introductionmentioning
confidence: 99%